Bridging Theory and Practice: The Role of Site Visits in Environmental Engineering Learning - Jusoh, Muhammad Noor Hazwan; Hadibarata, Tony (Tecno Scientifica Publisher, 2024)
In engineering education, experiential learning is essential as it allowed students to connect theoretical knowledge with real-world applications. This study explored the impact of industrial visits, a form of experiential learning, on engineering students’ comprehension, critical thinking, and overall educational experience. We employed a mixed-methods approach, integrating questionnaire surveys, reflective writing exercises, and qualitative analyses to assess the learning outcomes and pedagogical implications of these site visits. Our findings demonstrated that industrial visits significantly enhanced students’ understanding of engineering concepts by providing real-world context to theoretical knowledge. Through reflective exercises, students integrated their field trip experiences with classroom learning, fostering critical thinking abilities and a deeper comprehension of the subject matter. This study underscored the importance of curriculum integration. To nurture students as adept problem solvers and critical thinkers in both academic and practical engineering fields, fostering dynamic interactions between theoretical instruction and practical experiences was crucial. Our study encouraged further exploration of how experiential learning could enrich the educational journey, equipping students to tackle complex challenges in our ever-evolving environment as engineering education advanced.